Meningkatkan Keterampilan Menulis Karangan Sederhana Melalui Gambar Seri Pada Siswa Kelas III SD Inpres Onekore 6 Kecamatan Ende Tengah Tahun Pelajaan 2017/2018 - Dorothea Guru Embungganda (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
The study aimed at finding out the improvement of students’ writing skill in class III, Semester II SDN Montong Baan, academic year 2017/2018. Each cycle consists of four steps, namely are planning, executing, observing/evaluating, and reflecting. The method used is observation, questioner/test, and documentation. The result of the study shows that the achievement of Students in class III, Semester II SD Inpres Onekore 6, academic year 2017/2018 in learning bahasa Indonesia on writing a simple essay based on the serial pictures before the execution phase is very low. It is showed by the achievement of 57,92. After the execution of using serial pictures, the student achievement is better. It is showed in cycle 1, the result increases 67,78 with good category. In cycle 2, the result increases to 78,33% with good category.